Agent-Based Automatic Shore Operating Scheduling for a Container Terminal - Nannan Yan; Yuan Zhou (Institute of Advanced Engineering and Science, 2013)
This paper established berth allocation and quay crane scheduling models of shore operating for a container terminal. Furthermore, the structure of the berth - quay crane scheduling agent is also given. Finally, an example using genetic algorithm to resolve the berth allocation model and agent technology is shown. The experiment result shows that the use of intelligent theory and technology can provide an effective way for container terminal operating scheduling. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1989